The functional neurophysiological sequelae associated with high frequency dream recallers - van Wyk, Mariza (Department of Psychology, 2018)
Background: Dreaming is a universal experience, yet there is considerable inter-individual variability with regard to dream recall frequency (DRF). Research on DRF has been prolific leading to the development of various models delineating possible processes involved in dream recall. One such model is the 'arousal-retrieval' model positing that intra-sleep wakefulness is required for dream traces to be encoded into long-term storage, essentially proposing increased DRF as a product of a better memory for dreams. Results from recent studies support this model by demonstrating longer periods of intra-sleep wakefulness in high frequency recallers (HFRs) compared to low frequency recallers (LFRs). Furthermore, results showed heightened brain reactivity, as well as increased regional cerebral blood flow in areas in the brain associated with dream production. These results are indicative of the existence of a functional neurophysiological trait innate to HRs, while also supporting the premise that apart from a better memory for dreams, HRs also may produce more dreams. Awakenings from rapid eye movement (REM) sleep yield the highest dream recall rates, rendering REM sleep as a reasonable starting point for studying rates of dream production. Furthermore, increased dream production during REM sleep might also affect related processes, for example, leading to enhanced overnight emotional memory consolidation and emotion regulation. Hypotheses: The current study investigated the functional neurophysiological sequelae associated with HFRs in a design where HFRs are compared to LFRs. Hypotheses include: (1) HFRs will score significantly higher on certain personality dimensions; (2) HFRs will experience significantly more awakenings, as well as longer periods of intra-sleep wakefulness; (3) HFRs will have significantly higher rates of dream production as measured by the frequency of eye movements (REM density) during REM sleep; and (4) increased dream production during REM sleep will lead to enhanced overnight emotional memory consolidation and emotion regulation in HFRs. Methods: The study consisted of two groups of healthy young adults: high frequency recallers (n = 19) and low frequency recallers (n = 17) who underwent polysomnographic recordings on two non-consecutive nights. Memory tasks and affective questionnaires were completed before and after a night of sleep. Results: (1) HFRs scored significantly higher on the 'agreeableness' personality dimension and on the Boundary Questionnaire; (2) HFRs experienced significantly more awakenings, especially from stage 2 non-rem (NREM) sleep, as well as significantly longer periods of intra-sleep wakefulness; (3) no significant between-group differences with regard to REM density, nor (4) overnight emotional memory consolidation and emotion regulation were found. Conclusion: Results support, firstly, the proposition that certain personality traits, differences in sleep architecture, and increased DRF are an expression of a functional neurophysiological arrangement innate to HFRs. Secondly, the findings suggest that NREM sleep, as opposed to REM sleep, is important in relation to DRF in this specific population. This is the first study to not only replicate existing findings, but to also contribute to the extant literature by illuminating additional characteristics and features associated with HFRs.